The Relevance of Rahmah El-Yunusiyah's Philosophy in Strengthening the Character of Generation Z in the Digital Age - Nurhasanah, Aisyah; Shohib, Muhammad Wildan (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
The advancement of digital technology has affected the character development and psychological well-being of Generation Z, with young women experiencing increased exposure to social media. Insecurity, resulting from unrealistic beauty standards, social comparison, and appearance-related cyberbullying, has emerged as a significant issue in this context. These factors are associated with lower self-esteem, identity confusion, and unhealthy behaviors. This study evaluates the relevance of Rahmah El-Yunusiyah’s educational philosophy, as applied at Perguruan Diniyyah Puteri, in supporting the character, personality, and critical digital literacy of Generation Z young women. A qualitative approach was employed, using library research to analyze primary sources, including Rahmah El-Yunusiyah's official biography, as well as secondary sources such as academic journals and theoretical literature. The results show that Rahmah El-Yunusiyah's integrative educational model, which combines Islamic values, general knowledge, practical skills, and moral education through the tritunggal system, provides a suitable framework for addressing insecurity among Generation Z. The focus on taqwa, akhlaq, critical thinking, and social responsibility contributes to the development of a strong moral and identity foundation, supporting young women in managing digital challenges. Therefore, Rahmah El-Yunusiyah's educational philosophy remains relevant for addressing the psychological and moral challenges encountered by Generation Z in the digital era.